Oblicz :
(3 6/10 - 8/12 + 1/15 ) : (2 2/8 - 1/4 ) + 1,3​


Odpowiedź :

Obliczenia

[tex](3\frac{6}{10}-\frac{8}{12}+\frac{1}{15}):(2\frac{2}{8}-\frac{1}{4})+1,3=\\\\=(3\frac{3}{5}-\frac{2}{3}+\frac{1}{15}):(2\frac{1}{4}-\frac{1}{4})+1,3=\\\\=(3\frac{9}{15}-\frac{10}{15}+\frac{1}{15}):2+1,3=(2\frac{24}{15}-\frac{10}{15}+\frac{1}{15}):2+1,3=\\\\=(2\frac{14}{15}+\frac{1}{15}):2+1,3=2\frac{15}{15}:2+1,3=3:2+1,3=1,5+1,3=\boxed{2,8}[/tex]

Odpowiedź:

( 3 i 6/10 -8/12 + 1/15) : ( 2 i 2/8 -1/4) +1,3=

    = ( 3 i 3/5 -2/3+1/15) :( 2 i 1/4-1/4)+ 1 i 3/10=  (3 i 9/15 -10/15 +1/15) :2 +1 i 3/10=

=( 2 i 24/15  - 10/15+1/15) : 2 + 1 i 3/10= ( 2 i 14/15 + 1/15) :2 + 1 i 3/10=

   =3:2 + 1 i 3/10= 1 i 5/10 + 1 i 3/10= 2 i 8/10 = 2 i 4/5

Szczegółowe wyjaśnienie: